A DESCRIPTIVE STUDY ON STUDENTS’ ANXIETY IN SPEAKING SKILL AT SMP ISLAMIC SUNAN GUNUNGJATI - Wulan Wangi; Sindy Alfiatur Rofiah; Sutami Dwi Lestari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
Speaking is one of the important skills that must be mastered by students. Those who have low communication skills will have difficulty in expressing their thoughts, and they feel anxiety when they speak in front class. These problems should be addressed immediately. Based on these problem, the researchers conducted the study about finding the level of students' anxiety in speaking skills and the types of students' anxiety in speaking skills. The respondent in this study was the students in VII B at SMP Islamic Sunan Gunungjati. This study used a quantitative descriptive method. The instrument used in this study was a questionnaire sheet to obtain the instrument. Based on the results of the research, it can be concluded that the level of anxiety in students' speaking skills at SMP Islamic Sunan Gunungjati is